1999
DOI: 10.1093/molehr/5.5.433
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a functional fertilin-like ADAM plays a role in human spermoolemmal interactions

Abstract: Fertilin is a protein initially identified in guinea pig spermatozoa; it is the prototype of a larger family of conserved, proteins designated as a disintegrin and a metalloproteinase (ADAM). These heterodimers which consist of alpha and beta subunits, containing metalloproteinase-like and disintegrin-like domains, appear to play a role in mammalian fertilization. Peptides derived from the disintegrin domains of two ADAMs, fertilin and cyritestin, interfere with gamete adhesion and sperm-egg membrane fusion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…In the present study, we investigated the association between MYC, CYP19, ADAM2, PRM1 and PRM2 mRNA levels in spermatozoa and early embryo development in the pig using real-time PCR and IVF analyses. We focused on these mRNAs because it has been suggested that MYC, CYP19, ADAM2, PRM1 and PRM2 serve as markers of sperm motility and/or fertility in humans Naz et al 1991;Bronson et al 1999;Aquila et al 2002;Aoki et al 2006). The results of the IVF assays revealed that the ratio of blastocysts to cleaved embryos did not differ significantly between groups (Table 3; Table S2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we investigated the association between MYC, CYP19, ADAM2, PRM1 and PRM2 mRNA levels in spermatozoa and early embryo development in the pig using real-time PCR and IVF analyses. We focused on these mRNAs because it has been suggested that MYC, CYP19, ADAM2, PRM1 and PRM2 serve as markers of sperm motility and/or fertility in humans Naz et al 1991;Bronson et al 1999;Aquila et al 2002;Aoki et al 2006). The results of the IVF assays revealed that the ratio of blastocysts to cleaved embryos did not differ significantly between groups (Table 3; Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated whether the distribution of sperm mRNAs coding for MYC, aromatase (CYP19), fertilin-b (ADAM2), protamine 1 (PRM1) and protamine 2 (PRM2), which have been reported to be related to sperm quality or early embryo development in humans (Naz et al 1991;Bronson et al 1999;Aquila et al 2002;Aoki et al 2006), is involved in early embryonic development in the pig and whether a marker gene could be suggested to evaluate sperm quality in the pig. We also investigated whether the mRNA abundance of each gene changes after the induction of capacitation and whether these changes are involved in early embryonic development in the pig.…”
Section: Introductionmentioning
confidence: 99%
“…The role of fertilin ␤ in the fusion process is highlighted by the fact that sperm lacking this protein have a 50% decrease ability to fuse with the oocyte (Cho et al, 1998). In human, a peptide containing the integrin recognition sequence of human fertilin ␤ (Phe-Glu-Glu) was shown to also inhibit sperm adhesion to oocytes and their penetration (Bronson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are involved in sperm-oocyte penetration and sperm migration in the oviduct 37. In humans, ADAM 2 binds to the integrin receptor of oolemma (integrin Îą 6 β 1 ) and functions in sperm-oocyte interaction 29, 38. Additionally, ADAM 18 (tMDC III) contains the integrin binding motif which might be involved in sperm-oocyte binding in humans 39.…”
Section: Introductionmentioning
confidence: 99%